The Influence Of Leadership And Work Quality On Employee Performance With Employee Retention As An Intervening At ASN TK III Army Hospital dr. Reksodiwiryo Padang - I Nyoman Jaya Subrata; M.Chaerul Rizky (Yayasan Multidimensi Kreatif, 2024)
This study was conducted to see the influence of leadership and work quality on employee performance with employee retention as an intervention at Asn Hospital Tentara Tk III Dr. Reksodiwiryo Padang with this study researchers conducted this research on Jl. dr. Wahidin No.1, Ganting Parak Gadang, District Padang Timur Kota Padang, West Sumatra 25132. This study uses a type of quantitative research, and uses primary data sources, the population of this study is 75 employees and the sample used is all population so that it uses saturated sample techniques for research, data collection using questionnaire distribution methods and using phat analysis models as research models and using Smart PLS version 3 devices to calculate research results. The results of this study are as follows: Leadership has a positive and insignificant effect on employee performance with an original sample value of 0.059 and p values of 0.725. Work Quality has a positive and insignificant effect on Employee Retention with an original sample value of 0.123 with a p value of 0.538. Work Quality has a positive and insignificant effect on employee performance with an original sample value of 0.126 and p values of 0.289. Employee retention has a positive and significant effect on Employee Performance with a value of 0.783 and p values of 0.000. Leadership has a positive and significant effect on Employee Retention with an original sample value of 0.841 and a p value of 0.000. Leadership influences Employee Performance through Employee Retention positively and significantly with original sample values of 0.658 and p values of 0.000. Work Quality has an indirect effect on Employee Performance through Employee Retention in a positive insignificant manner with an original sample value of 0.096 and p values of 0.540.